2019
DOI: 10.1039/c9ra01973a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on methane hydrate formation in silica gel particles below the freezing point

Abstract: Herein, methane hydrate formation in silica gel was studied in the temperature and pressure range of 253.1–268.1 K and 4.0–6.0 MPa, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Furthermore, experiments at 276 K (Figure A4.5) also showed a similar trend as observed at 269 K and 274 K, with higher gas uptake at 130% pore-volume saturation (73.5 mmol CH4/mol H2O) than at 200% pore-volume saturation (72.9 mmol CH4/mol H2O). As anticipated, the CH4 uptake decreased with an increase in temperature from 269 K to 276 K, which indicates the influence of the driving force, and a similar trend was also observed in porous silica gel particles [178]. However, it is also important to mention that the experiments with 70% and 100% pore-volume saturations at 276 K failed to nucleate despite having a driving force of 2.7 MPa.…”
Section: Ch4 Hydrate Kineticssupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, experiments at 276 K (Figure A4.5) also showed a similar trend as observed at 269 K and 274 K, with higher gas uptake at 130% pore-volume saturation (73.5 mmol CH4/mol H2O) than at 200% pore-volume saturation (72.9 mmol CH4/mol H2O). As anticipated, the CH4 uptake decreased with an increase in temperature from 269 K to 276 K, which indicates the influence of the driving force, and a similar trend was also observed in porous silica gel particles [178]. However, it is also important to mention that the experiments with 70% and 100% pore-volume saturations at 276 K failed to nucleate despite having a driving force of 2.7 MPa.…”
Section: Ch4 Hydrate Kineticssupporting
confidence: 78%
“…Another alternative approach to enhance the kinetics of CH4 hydrate formation rate is by employing a fixed bed porous column without stirring and some of the existing research has already shed light on suitable fixed bed packings to enhance water-to-hydrate conversion and to boost the hydrate growth [127,168,170,175,177,178,180,181,184,186,187,190,191,193,194,196,197,219,228,229,266,370,. Developing a synthetic porous material with high storage capacity, high chemical, mechanical, and thermal stability is assumed to be vital for a successful and efficient storage process.…”
Section: Introductionmentioning
confidence: 99%
“…When the ice particles are wrapped by the hydrate shell, the hydrate formation process turns to the diffusion control stage, and the shell surface forms bulges during the hydrate formation process and gradually thickens 43 . This causes the pore channels between the ice powder to become smaller and cement gradually 44 . These results demonstrated that, the agglutination among the smaller particle size ice powder hindered the diffusion process of gas in the mixture system of quartz sand and ice powder.…”
Section: Resultsmentioning
confidence: 93%
“…43 This causes the pore channels between the ice powder to become smaller and cement gradually. 44 These results demonstrated that, the agglutination among the smaller particle size ice powder hindered the diffusion process of gas in the mixture system of quartz sand and ice powder. The smaller the particle size of ice powder was, the more serious the effect would be.…”
Section: Effects Of Temperature and Ice Powder Particle Size On The F...mentioning
confidence: 88%
“…Additionally, morphological and physical properties of the host sediments could inuence the kinetics of hydrate formation and dissociation. [38][39][40][41][42][43] The formation kinetics and ability of conned water into hydrates under the gas-rich environment is studied.…”
Section: Introductionmentioning
confidence: 99%